Toxicity trial of canine posterior cricoarytenoid intramuscular vincristine injections. (8th December 2017) - Paniello, Randal C.; Bhatt, Neel K.; Chernock, Rebecca
Abstract : Objectives/Hypothesis: In animal studies, intramuscular vincristine injections have been shown to block reinnervation of the denervated target muscle. This application could be used selectively to influence recovery patterns following injury of recurrent laryngeal nerves (RLNs). However, vincristine is currently Food and Drug Administration approved only for intravenous use. A formal toxicity trial of intramuscular injections was performed. Study Design: Animal study. Methods: Sixteen female canines underwent direct laryngoscopy with injection of moderate‐ (0.4 mg, n = 8) or high‐dose (0.6 mg, n = 8) vincristine into the posterior cricoarytenoid (PCA) muscles. Plasma samples were collected at various time points postinjection and vincristine levels determined. At 24 hours (n = 7) or 14 days (n = 9) postinjection, animals were anesthetized and videolaryngoscopy documented vocal fold mobility and mucosal appearance. Adductor function was measured during stimulation of the RLN. Larynges were processed for histology. Results: Fifteen minutes after injection, plasma vincristine levels averaged 10.2% ± 6.7% of the intravenous maximum, suggesting about 90% of the vincristine remained within the PCA muscle. Plasma levels were usually below detectable limits within 24 hours. At the end points, all animals had grossly normal‐appearing mucosa and full range of motion. Laryngeal adductor strength was normal in all cases. Histology showed moderate to severe acute inflammation in the submucosa only in the high‐dose group at 24 hours. There was no necrosis of muscle or mucosa. Conclusions: Intramuscular vincristine injections into the canine PCA muscles resulted in no significant local toxicity, even at the maximum dose. It would be reasonable to evaluate this treatment strategy in a phase I human trial. Level of Evidence: NA Laryngoscope, 128:E247–E250, 2018